EFFORTS TO STRENGTHEN THE RELIGIOUS CHARACTER OF THE TEENS OF THE BAITURRAHIM MOSQUE THROUGH RELIGIOUS ACTIVITIES IN KOPONG DUSUN SEBANGUN, SAMBIK BANGKOL VILLAGE, GANGGA DISTRICT - halid budiawan (JOETAL: Journal of Education, Teaching and Learning, 2024)
This research is motivated by the fact that there are still teenagers whose morals are still not good, this can be seen from the behavior of teenagers who still say dirty words, impolite behavior when talking to older people, consuming alcohol, and lack of enthusiasm among teenagers. This research aims to determine efforts to strengthen the religious character of teenagers, the supporting and inhibiting factors for efforts to strengthen the religious character of teenagers. This type of research uses descriptive qualitative research. Research data was obtained through observation, interviews and documentation techniques. The data analysis techniques used in this research are data reduction (data reduction), data presentation (data presentation), and verification (drawing conclusions). The data validity techniques used are increased persistence and triangulation. The results of this research show that: 1) efforts to strengthen the religious character of teenagers at the Baiturrahim mosque are carried out through religious activities, there are weekly programs, namely joint yasinan, al-barzanji reading. Monthly activities are monthly recitations which are held once a month and annual activities such as isro'mi'roj, the Prophet's birthday, and other PHBI activities.  2) Supporting factors for strengthening the religious character of teenagers at the Baiturrahim Mosque, namely support from the family and the existence of a good relationship between parents and administrators. Factors hampering the implementation of the implementation of the religious character of teenagers at the Baiturrahim Mosque are free association and economic conditions.